1.33+9x-6=12

Simple and best practice solution for 1.33+9x-6=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.33+9x-6=12 equation:


Simplifying
1.33 + 9x + -6 = 12

Reorder the terms:
1.33 + -6 + 9x = 12

Combine like terms: 1.33 + -6 = -4.67
-4.67 + 9x = 12

Solving
-4.67 + 9x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4.67' to each side of the equation.
-4.67 + 4.67 + 9x = 12 + 4.67

Combine like terms: -4.67 + 4.67 = 0.00
0.00 + 9x = 12 + 4.67
9x = 12 + 4.67

Combine like terms: 12 + 4.67 = 16.67
9x = 16.67

Divide each side by '9'.
x = 1.852222222

Simplifying
x = 1.852222222

See similar equations:

| 7b+3b-9b=20 | | x^2+12x+y^2-14y-204=0 | | 6x-15=3x+9 | | 40-2x=14-9x | | x^2+12x+y^2+14y-204=0 | | 5x+8=-32-5x | | b-b+4b+2b-5b=19 | | 30+2a=3-7(3+2a) | | 14q-12q+q-2q=17 | | .40x=485.82 | | -3x-8=2(8x-4) | | .28x=36320 | | 28-x=3x-94 | | 8x+2+3x=-9 | | log(x-22)=3 | | M(3-4m)=7+4(3-m^2) | | 1-8v-4v=-11 | | y=3-2(8) | | 5-(2x+5)=30 | | 5(5b-3)=25b | | sovwlnx^2=13 | | 7m+5-5m=-2+m-9 | | -92=-8-6(2-4x) | | -2x+34=2x+6 | | 84=6(7-7x) | | -3(y+4)-6=22 | | x+12=4x+3 | | f(15)=50 | | (2x+1)-(7x+5)= | | x=-2.5+.625y | | (x+2/3)*4=16/3 | | y=3-2*8 |

Equations solver categories